Spline and Spline Wavelet Methods with Applications to Signal and Image Processing Volume III: Selected Topics - Averbuch, Amir Z.; Neittaanmäki, Pekka; Zheludev, Valery A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book provides a practical guide, complete with accompanying Matlab software, to many different types of polynomial and discrete splines and spline-based wavelets, multiwavelets and wavelet frames in signal and image processing applications. In self-contained form, it briefly outlines a broad range of polynomial and discrete splines with equidistant nodes and their signal-processing-relevant properties. In particular, interpolating, smoothing, and shift-orthogonal splines are presented. .
Chapter 1. Introduction: Periodic Signals and Filters -- Chapter 2. Periodic Polynomial Splines -- Chapter 3. Periodic Discrete and Discrete-time Splines -- Chapter 4. Periodic Orthogonal Wavelets and Wavelet Packets -- Chapter 5. Two-dimensional Orthogonal Wavelets and Wavelet Packets -- Chapter 6. Local Splines on Non-uniform Grid -- Chapter 7. Spline-based Wavelet Transforms -- Chapter 8. Biorthogonal Wavelet Transforms Originating from Discrete and Discrete-time Splines -- Chapter 9. Wavelet Frames Generated by Spline-based p-ﬁlter Banks -- Chapter 10. Snapshot Spectral Imaging -- Chapter 11. Delineation of Malignant Skin Tumors by Hyperspectral Imaging -- Chapter 12. Acoustic Detection of Moving Vehicles -- Chapter 13. Detection of Incipient Bearing Fault in a Slowly Rotating Machine Using Spline Wavelet Packets.
Keywords: Signal processing; Image processing -- Digital techniques; Computer vision; Engineering design; Algorithms; Signal, Speech and Image Processing; Computer Imaging, Vision, Pattern Recognition and Graphics; Engineering Design; Algorithms